PERBEDAAN KADAR HEMOGLOBIN DAN BERAT BADAN IBU HAMIL TRIMESTER III BERDASARKAN KEPATUHAN MENGONSUMSI TABLET ZAT BESI - Simanjuntak, Netti Meilani; Sembiring, Rinawati; Septaria, Niasti (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
High Maternal Mortality Rate can also be related to anemia. The results of Riskesdas 2018 show that the proportion of anemia in pregnant women from 2013 to 2018 has increased by 11.8%, in 2013 it showed the proportion of 37.1% and in 2018 it showed the proportion of 48.9%. One of the efforts to reduce the prevalence of anemia is by giving 90 tablets of iron (Fe) during pregnancy. This study aims to determine the differences in hemoglobin levels and body weight of third trimester pregnant women based on compliance with consuming iron tablets in the working area of the Teluk Desa Puskesmas in 2021. This study uses a comparative quantitative approach. The number of samples of this study were 106 third trimester pregnant women. The sampling technique used was purposive sampling. The results showed a 2-way (t-tailed) significance value of 0.000. <0.05 and 0.003 <0.005. This means that there is a significant difference in hemoglobin levels and body weight of pregnant women between mothers who are compliant and do not comply with consuming iron tablets during pregnancy. This study recommends that medical personnel (midwives or nurses), especially those in the health center KIA clinic, can improve the quality of information regarding compliance with iron consumption in pregnancy so that risk factors for anemia can be overcome